The Relationship Between Cognitive Function and Life Space: The Potential Role of Personal Control Beliefs - Sartori, Andrea C. (2011)
We examined the relationship of cognitive and functional measures with life space (a measure of spatial mobility examining extent of movement within a person’s environment) in older adults, and investigated the potential moderating role of personal control beliefs. Internal control beliefs reflect feelings of competence and personal agency, while attributions of external control imply a more dependent or passive point of view. Participants were 2,737 adults from the ACTIVE study, with a mean age of 74 years. Females comprised 76% of the sample, with good minority representation (27% African American). In multiple regression models controlling for demographic factors, cognitive domains of memory, reasoning, and processing speed were significantly associated with life space (p<.001 for each), and reasoning ability appeared most predictive (B=.117). Measures of everyday function also showed significant associations with life space, independent from the traditional cognitive measures. Interactions between cognitive function and control beliefs were tested, and external control beliefs moderated the relationship between memory and life space, with the combination of high objective memory and low external control beliefs yielding the highest life space (t=−2.07; p=.039). In conclusion, older adults with better cognitive function have a larger overall life space. Performance-based measures of everyday function may also be useful in assessing the functional outcome of life space. Additionally, subjective external control beliefs may moderate the relationship between objective cognitive function and life space. Future studies examining the relationships between these factors longitudinally appear worthwhile to further elucidate the interrelationships of cognitive function, control beliefs, and life space.